2018
DOI: 10.1186/s12885-018-4303-z
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib for advanced sarcoma: results from multiple institutions’ off-label use in China

Abstract: BackgroundAnti-angiogenesis Tyrosine kinase inhibitors (TKIs) have been proved to show promising effects on prolonging progression-free survival (PFS) for advanced sarcoma after failure of standard multimodal Therapy. Methylsulfonic apatinib is one of those TKIs which specifically inhibits VEGFR-2. This paper summarizes the experience of three Peking University affiliated hospitals in off-label use of apatinib in the treatment of extensively pre-treated sarcoma.MethodsWe retrospectively analysed files of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
77
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 30 publications
9
77
0
1
Order By: Relevance
“…NCT02243605) in patients with EWS look promising, and an ORR of 28.1% in 32 patients was observed, as well as a high tumor burden reduction rate of 71% (38). For apatinib, which is also a strong aaTKI (39), an ORR of 70% (7/10) was observed in an off-label set of patients with EWS (33). Based on these data, it was concluded that aaTKIs require further investigation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…NCT02243605) in patients with EWS look promising, and an ORR of 28.1% in 32 patients was observed, as well as a high tumor burden reduction rate of 71% (38). For apatinib, which is also a strong aaTKI (39), an ORR of 70% (7/10) was observed in an off-label set of patients with EWS (33). Based on these data, it was concluded that aaTKIs require further investigation.…”
Section: Discussionmentioning
confidence: 92%
“…Only regorafenib, which has a stronger anti-angiogenesis effect, demonstrated promising clinical activity in patients with EWS. Further trials for other types of aaTKI, including pazopanib, cabozantinib and apatinib, which have shown some activity in other types of sarcoma (31)(32)(33), are ongoing and the results of which are anticipated. For patients who were refractory to first-line chemotherapy, pazopanib was reported to be effective in a set of case series (34-37).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The apatinb was applied on prolonging progression-free survival of advanced sarcoma when the standard multimodal therapy was failure. 3 In previous research, the clinical presentation of apatinib in advanced non-small-cell lung cancer showed its effective and well tolerated in patients. 4 Most studies have shown that apatinib has encouraging efficacy and controllable side effects in the treatment of a variety of solid tumor.…”
Section: Introductionmentioning
confidence: 98%
“…Apatinib is the world's first small‐molecule‐drug of selective vascular endothelial growth factor receptor‐2 tyrosine kinase inhibitor (TKI) that is proven to be safe and effective in advanced or metastatic gastric cancer . The apatinb was applied on prolonging progression‐free survival of advanced sarcoma when the standard multimodal therapy was failure . In previous research, the clinical presentation of apatinib in advanced non‐small‐cell lung cancer showed its effective and well tolerated in patients .…”
Section: Introductionmentioning
confidence: 99%
“…1 Anti-angiogenesis tyrosine kinase inhibitors (TKIs) are effective in prolonging progression-free survival (PFS) for advanced osteosarcoma that has progressed upon firstor second-line chemotherapy. 2,3 In a prospective study on apatinib for advanced osteosarcoma after the failure of traditional multimodal therapy (NCT02711007), apatinib reached 4-month PFS rate of 56.8% for advanced osteosarcoma [4][5][6][7] with a tolerable and manageable safety profile. 5,[8][9][10] The administration of apatinib induced tumor shrinkage and showed a high objective response (43.2%), but the toxic effects were severe with high rates of dose reduction (59.5%).…”
Section: Introductionmentioning
confidence: 99%